Assessment of antibacterial, anti-inflammatory, and cytotoxic effects of different extracts of Gynura procumbens leaf - Md. Ziaul Amin, Ph.D; Mitu Afrin, MS; Nigar Sultana Meghla, MS; Md. Ashaduzzaman Nur, MS; Md. Mashiar Rahman, Ph.D; M. Jashim Uddin, MS (Elsevier, 2021)
ABSTRACT: Background: In Southeast Asia, Gynura procumbens has been utilized as a traditional medicinal herb for many diseases. The nontoxic effects of the leaves of G procumbens can be consumed safely for the treatment of many diseases, especially diabetes mellitus. Objectives: This study aimed to assess the antibacterial, anti-inflammatory, and cytotoxic effects of G procumbens leaves through different extracts. Methods: Cold extraction was employed for G procumbens leaves. Disc diffusion, bovine serum albumin denaturation, brine shrimp lethality assays, and microscopic examination of tissues (ie, liver, kidney, and heart) were performed to measure antibacterial, anti-inflammatory, and cytotoxic activities, and histopathologic analysis, respectively. Results: The distinct concentrations of aqueous, ethanol, and n-hexane extracts showed prominent antibacterial activity against four pathogenic bacterial strains (Chromobacterium sp, Staphylococcus aureus, Enterococcus faecium, and Escherichia coli 0157:H7:LT). The aqueous extract of G procumbens at a concentration of 200 µg/mL showed potential antibacterial activities against S aureus and E faecium, with mean (SD) zones of inhibition of 15 (1.0) mm and 10 (0.55) mm, respectively. At a concentration of 40 µg/mL, the aqueous extract of G procumbens exhibited significant (P < 0.01) anti-inflammatory activity compared with that of the other 2 extracts in the bovine serum albumin denaturation assay. The n-hexane extract showed moderate cytotoxic activity compared with that of vincristine sulfate. The median lethal concentration values of the aqueous, ethanol, and n-hexane extracts were 427.66, 218.56, and 114.51 μg/mL, respectively. The aqueous extract exhibited lower cytotoxicity than that exhibited by the ethanol and n-hexane extracts. The histopathologic analysis results showed that the aqueous extract of G procumbens had no harmful effects on the different organs of the experimental mice. Conclusions: The aqueous extract of G procumbens could be a potential source for treating various infectious and chronic diseases. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)